Quantizing, recognizing, and characterizing the recycling potential of recyclable waste in China: A field tracking study of Suzhou. (10th November 2018) - Gu, Binxian; Li, Yuanyuan; Jin, Dawei; Yi, Siqiang; Gu, Aijun; Bu, Xing you; Zhou, Hua; He, Sheng; Cheng, Rong; Jia, Renfu
Abstract: Promoting recycling is one of the best effective measures to relieve contradictions such as "waste siege" and resource shortage in China. To do that, quantifying and recognizing the recycling potential (RCP) of recyclable waste (RCW) are foundations. This study quantifies the RCP of RCW (RCP-RCW) in Suzhou, a typical developed city in East China, based on a systematic tracking survey for one week in each season and in different districts starting from the summer of 2011 to the spring of 2017. Results show that Suzhou's RCP-RCW was 92.7 (89.3–96.0), with a 90% confidence interval percentage, among which, recyclable organics and recyclable material (RCM) accounted for 55.1% and 37.6%, respectively. In RCMs, a high RCM recovery value and low RCM recovery value accounted for 64.8% and 26.0%, respectively. RCW generation was 242.4 thousand tons in 2016 and is expected to reach 738.8 thousand tons in 2030. Moreover, spatiotemporal variation of RCW was characterized. Factors, such as local customs and culture, dietary habits, residential lifestyles and consumption structure influence the RCW stream generation. All the obtained results can improve the knowledge base for effectively promote recycling, and contribute to making governmental policy and the recycling industry's business development in Suzhou and other Chinese cities. Graphical abstract: Image 1 Highlights: Recycling potential of recyclable waste (RCW) were quantitated. RCWs generation trends were estimated. Recommendations for recycling were proposed.